1999
DOI: 10.1677/joe.0.1620259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IGF-I combined with GH on glucocorticoid-induced changes of bone and connective tissue turnover in man

Abstract: Chronic glucocorticoid therapy results in negative bone and connective tissue balance. To assess the effects of GH and a combination of IGF-I and GH, 24 healthy male volunteers received in a double blind fashion either recombinant human GH (0·3 IU/kg per day s.c.), or a combination of GH (0·3 IU/kg per day s.c.) and IGF-I (80 µg/kg per day s.c.) or placebo (saline s.c.) during 6 days of methylprednisolone (0·5 mg/kg per day) treatment. Methylprednisolone decreased serum osteocalcin concentrations during placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
2
10
0
1
Order By: Relevance
“…Despite the well known fact that glucocorticoids decrease hydroxyproline levels and increase connective tissue turnover [16,17], it was shown in the 1990s that they also increase matrix protein production and matrix maturation. In a study by Del Monaco et al, glucocorticoids were shown to induce up-regulation of human elastin promoter activity and regulate gene expression at the transcriptional level [11].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the well known fact that glucocorticoids decrease hydroxyproline levels and increase connective tissue turnover [16,17], it was shown in the 1990s that they also increase matrix protein production and matrix maturation. In a study by Del Monaco et al, glucocorticoids were shown to induce up-regulation of human elastin promoter activity and regulate gene expression at the transcriptional level [11].…”
Section: Discussionmentioning
confidence: 99%
“…On the whole, IGF-I therapy resulted in significantly increased bone turnover and improved bone formation, with no significant adverse effects reported (Locatelli and Bianchi, 2014). IGF-I administration has been studied in healthy subjects (Bianda et al, 1997; Ghiron et al, 1995; Mauras et al, 1996), fasting subjects (Grinspoon et al, 1995), anorexic/osteopenic subjects (Grinspoon et al, 2002, 1996; Misra et al, 2009), postmenopausal women with and without osteoporosis (Ebeling et al, 1993; Friedlander et al, 2001), osteopenic men (Johansson et al, 1996, 1992), subjects with osteoporosis secondary to Werner syndrome (Rubin et al, 1994), and subjects with glucocorticoid-induced osteoporosis (Berneis et al, 1999). The only study which did not find any differences between IGF-I treatment and placebo (Friedlander et al, 2001) was a relatively long-term study in which negative feedback from exogenous IGF-I could have suppressed GH secretion.…”
Section: Gh/igf Therapymentioning
confidence: 99%
“…An increase in serum osteocalcin, carboxy-terminal propeptide of type I procollagen and carboxy-terminal telopeptide of type I collagen was observed following shortterm recombinant human (rh)GH treatment in a selected population of patients receiving chronic corticosteroid treatment for non-endocrine diseases (27). Moreover, combined therapy of rhGH and rhIGF-I counteracted selected negative effects of glucocorticoids on bone in healthy volunteers who received short-term glucocorticoid therapy (29). Observational and controlled studies in children receiving glucocorticoid therapy for juvenile idiopathic arthritis showed that rhGH restored normal height velocity with a concomitant improvement of bone mineralization (30)(31)(32)(33).…”
Section: Extraskeletal Effects Of Glucocorticoids On Bone Metabolismmentioning
confidence: 99%